A survey of the management of patients with temporomandibular disorders by general dental practitioners in southern Brazil - Aldrigue, Raquel Haidê Santos; Sánchez-Ayala, Alfonso; Urban, Vanessa Migliorini; Pavarina, Ana Claudia; Jorge, Janaina Habib [UNESP]; Campanha, Nara Hellen (Wiley, 2014)
Purpose: Temporomandibular disorders (TMD) are recognized as one of the mostcontroversial topics in dentistry, despite the fact that both basic science and clinicalresearchers have currently reached some degree of consensus. This study aimed toconduct a questionnaire-based survey about the management of TMD patients bygeneral dental practitioners (GDPs).Materials and Methods: One hundred fifty-one GDPs with a private practice in a cityof southern Brazil were included, independent of school of origin, gender, graduationyear, and curriculum content. All participants were administered a questionnaire aboutthe management of patients with TMD, and the responses were analyzed by binomialand chi-square tests (α = 0.05).Results: Of the GDPs, 88.7% received TMD patients, who were primarily diagnosedon the basis of medical history (36.6%) or physical examination (30.4%). Of these,65.4% referred the patients elsewhere, primarily to specialists in occlusion (36.1%) ororthodontics (29.7%). Occlusal splinting was the most commonly used managementmodality (20.8%), followed by occlusal adjustment (18.1%) and pharmacotherapy(16.6%). Splints were fabricated in maximum habitual intercuspation or centric re-lation depending on individual patient (54.8%). The hard stabilization form was themost common type of appliance used (35.0%). Moreover, 73.8% of the GDPs didnot employ semi-adjustable articulators, and 69.5% adjusted the appliances at thetime of fixing. The duration of splint use and the frequency of follow-up were con-sidered patient dependent by 62.1% and 72.8%, respectively. GDPs considered thetwo major TMD etiologic categories as multifactorial (20.8%) and occlusion (19.9%).Multidisciplinary medical and dental treatment was considered necessary by 97.9%.Conclusions: The evaluated general dental practitioners manage TMD patients ac-cording to international guidelines.
Keywords: Temporomandibular disorders